2022
DOI: 10.1097/im9.0000000000000081
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Amoxicillin Use in Fever Clinic Patients: Standardized Application of Antibiotics is Still Challenging

Abstract: Amoxicillin is widely used by the Chinese population and available in pharmacies without prescription. We performed a retrospective study on patients with fever who took amoxicillin before going to the fever clinic of the Second Affiliated Hospital of Nanchang University from March 1, 2020 to March 31, 2021. Among the total of 9093 patients attending the fever clinic, 446 patients had a history of taking amoxicillin, from which 100 cases were randomly selected to evaluate the therapeutic effects of non-prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Amoxicillin is widely used by the Chinese population and can be obtained in pharmacies without a prescription. However, Yu et al 13 found that there was no significant difference in symptom improvement, leukocyte, neutrophil or lymphocyte counts or C-reactive protein levels between the patients taking amoxicillin and the controls. It shows that although over-the-counter amoxicillin is widely used in patients with fever, it does not provide significant beneficial therapeutic effects.…”
mentioning
confidence: 96%
“…Amoxicillin is widely used by the Chinese population and can be obtained in pharmacies without a prescription. However, Yu et al 13 found that there was no significant difference in symptom improvement, leukocyte, neutrophil or lymphocyte counts or C-reactive protein levels between the patients taking amoxicillin and the controls. It shows that although over-the-counter amoxicillin is widely used in patients with fever, it does not provide significant beneficial therapeutic effects.…”
mentioning
confidence: 96%